Blockade of NaV1.8 Increases the Susceptibility to Ventricular Arrhythmias During Acute Myocardial Infarction - Qi, Baozhen; Dai, Shimo; Song, Yu; Shen, Dongli; Li, Fuhai; Wei, Lanfang; Zhang, Chunyu; Nie, Zhenning; Lin, Jiaxiong; Cai, Lidong; Ge, Junbo (Frontiers in Cardiovascular Medicine, 2021)
SCN10A/NaV1.8 may be associated with a lower risk of ventricular fibrillation in the setting of acute myocardial infarction (AMI), but if and by which mechanism NaV1.8 impacts on ventricular electrophysiology is still a matter of debate. The purpose of this study was to elucidate the contribution of NaV1.8 in ganglionated plexi (GP) to ventricular arrhythmias in the AMI model. Twenty beagles were randomized to either the A-803467 group (n = 10) or the control group (n = 10). NaV1.8 blocker (A-803467, 1 μmol/0.5 mL per GP) or DMSO (0.5 mL per GP) was injected into four major GPs. Ventricular effective refractory period, APD90, ventricular fibrillation threshold, and the incidence of ventricular arrhythmias were measured 1 h after left anterior descending coronary artery occlusion. A-803467 significantly shortened ventricular effective refractory period, APD90, and ventricular fibrillation threshold compared to control. In the A-803467 group, the incidence of ventricular arrhythmias was significantly higher compared to control. A-803467 suppressed the slowing of heart rate response to high-frequency electrical stimulation of the anterior right GP, suggesting that A-803467 could inhibit GP activity. SCN10A/NaV1.8 was readily detected in GPs, but was not validated in ventricles by quantitative RT-PCR, western blot and immunohistochemistry. While SCN10A/NaV1.8 is detectible in canine GPs but not in ventricles, blockade of NaV1.8 in GP increases the incidence of ventricular arrhythmias in AMI hearts. Our study shows for the first time an influence of SCN10A/NaV1.8 on the regulation of ventricular arrhythmogenesis via modulating GP activity in the AMI model.